Beta-Secretase 1 Underlies Reactive Astrocytes and Endothelial Disruption in Neurodegeneration - Chacón-Quintero, María Victoria; Pineda-López, Lina Gisela; Villegas-Lanau, Carlos Andrés; Posada-Duque, Rafael; Cardona-Gómez, Gloria Patricia (Frontiers in Cellular Neuroscience, 2021)
Dysfunction in the neurovascular unit (NVU) is a key component in the progressive deterioration of Alzheimer's disease (AD) and is critical in vascular dementia. Recent studies have shown that inflammation plays early and perhaps causal roles in the pathogenesis of AD related to NVU damage, possibly in part by overactivating the aspartic acid protease activity of β-site amyloid precursor protein-cleaving enzyme 1 (BACE1), which until now has almost solely been studied in the context of the β-amyloid cascade. In this study, we analyzed the relationship of BACE1 with astrocytes and blood vessels in human brains with sporadic and familial dementia (Autosomal dominant cerebral arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), sporadic Alzheimer's disease (SAD), and familial Alzheimer's disease (FAD)) and how BACE1 inhibition affects astrocytes and endothelial cells under conditions of glutamate toxicity. Our results show increased BACE1, PHF (Pair helicoidal filaments)-tau and GFAP (Glial Fibrillary Acid Protein) immunoreactivity (IR) in the CA1 hippocampal regions of FAD and SAD brains. Furthermore, BACE1 immunoprecipitated with GFAP in tissue samples from all study cases, but their immunofluorescence close to (10 µm3) or overlapping blood vessels was only increased in FAD and SAD brains, and PHF-tau was present around the vessels mainly in FAD brains. Interestingly, the increased BACE1 levels were associated with reactive astrocytes, characterized by morphological changes and upregulation of GFAP under pathological and stressful conditions, and endothelial disruption by glutamate excitotoxicity, and these effects were reversed by BACE1 inhibition; further, BACE1-inhibited astrocytes protected endothelial cell integrity by preserving zonula occludens-1 (ZO-1) distribution and decreasing the expression of inflammatory markers. Taken together, these findings suggest that BACE1 dysregulation in astrocytes may have a role in the alterations in NVU integrity implicated in neurodegeneration.